The Theme of the Black Sea in the Literary Interpretations of Yevhen Malanyuk - Bahan, Oleh (Poznańskie Studia Slawistyczne, 2024)
The article interprets artistic images on the theme of the Black Sea in the work of the iconic Ukrainian poet and thinker of the interwar period – Yevhen Malanyuk. Emphasis is placed on the expressiveness of the artistic thinking of Malanyuk, who managed to create bright and multifaceted images-symbols and images-concepts regarding the mental and civilizational attraction of the Ukrainian ethnic group to the Black Sea. It is traced how the author substantiated his poetic visions with deep theoretical reflections in historiosophical and cultural essay writing. The central idea of the writer: the Black Sea was and is an important geopolitical and geocultural frontier for the Ukrainian ethnic group and its state. It is explained why Malanyuk believed that the Hellenistic and Scythian-Sarmatian archetypes from Ukrainian ethnogenesis determined the peculiarities of the Ukrainian psychotype.